Socio-economic Exclusion in Nepal: A Regional Perspective - Panta, Krishna Raj (Economic Journal of Nepal, 2015)
This paper examines how exclusionary development policy produces regional disparities in public services that hinder people’s access to basic facilities, which leads to the unequal quality of life of people among the different regions in Nepal. The study, using secondary data and simple descriptive statistical tools of analysis, finds that- in comparison to central region and urban sector, Mountain, Midwestern and Far Western regions, as well as the rural sector of the country, are excluded from national development policies and programmes leading to the low standard of living of people of those regions characterized by low human development and high poverty. The Economic Journal of Nepal, Vol. 35, No. 3, July-September 2012 (Issue N0. 139)